Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1990
DOI: 10.1111/j.1469-7610.1990.tb01577.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour and Personality in Childhood as Predictors of Adult Psychiatric Disorder

Abstract: Associations between childhood behaviour and personality and adult affective disorder were investigated in a 36-year follow-up of a national birth cohort. A number of early characteristics were significantly related to adult outcome including enuresis, nailbiting, speech problems, truancy and composite indices of behaviour and personality. Continuity was not explained by factors acting independently on child and adult measures. Prediction of adult disorder, although better for women, was modest in both sexes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
50
1
2

Year Published

1995
1995
2015
2015

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(60 citation statements)
references
References 43 publications
5
50
1
2
Order By: Relevance
“…However, results from a longitudinal study of a British birth cohort suggest that neuroticism is unrelated to participation, while having a psychiatric disorder predicted a slightly higher participation rate. 15 The frequency of short alleles in the present study was very close to that reported by Lesch et al (43.5% vs 43%) in a predominantly Caucasian sample, 1 but much lower than the frequency in Japanese samples (77% and 83.3%), 4,6 and slightly lower than an Israeli sample (53%). 3 There appear to be major ethnic differences which are a potential confounding factor in association studies of the 5-HTTLPR.…”
supporting
confidence: 72%
“…However, results from a longitudinal study of a British birth cohort suggest that neuroticism is unrelated to participation, while having a psychiatric disorder predicted a slightly higher participation rate. 15 The frequency of short alleles in the present study was very close to that reported by Lesch et al (43.5% vs 43%) in a predominantly Caucasian sample, 1 but much lower than the frequency in Japanese samples (77% and 83.3%), 4,6 and slightly lower than an Israeli sample (53%). 3 There appear to be major ethnic differences which are a potential confounding factor in association studies of the 5-HTTLPR.…”
supporting
confidence: 72%
“…Pathways from childhood to adult life As at age 36, measures of adolescent behaviour mediated some of the effect of family background (Rodgers, 1990b). In particular, the effect of maternal neuroticism on the symptom score was reduced to nonsignificance.…”
Section: Adult Health and Social Circumstancesmentioning
confidence: 99%
“…Earlier research on this cohort demonstrated a link between adult affective disorder (as measured by the Present State Examination) at 36 years and measures of the early environment (Rodgers, 1990a) and childhood behaviour and temperament (Rodgers, 1990b). Measures of early behaviour were more strongly associated with adult symptoms than the environmental measures and suggested that childhood and adolescent behaviour and personality mediated the long term effects of the early environment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it seems that the obtained figures are similar in developed countries. The rate of behavioral problems varies with the age of the children (11). The results of a study showed that the rate of aggression varied from 9-10% (12).…”
Section: Discussionmentioning
confidence: 99%